Análisis de la evolución de los parámetros ambientales en la central de generación eléctrica de la ciudad de Contamana 2018 - 2021, región Loreto - 2022 - Alva Flores, Liz Sofia (2022)
The thesis was developed in the Power Plant of the city of Contamana, to analyze the evolution of environmental parameters, from the environmental monitoring of 2018-2021. The research design is non-experimental. The information was obtained from the biannual Monitoring Reports of the Environmental Parameters of the Power Plant. Variations in the data from 15 quarterly environmental monitoring (04 years) were systematized and analyzed, making an analysis of trends and prediction of changes in environmental parameters using the Holt-Winters Model. The Analysis of the environmental parameters show us values that, for the most part, have regular behavior and that are below the environmental quality standards according to current regulations; Mentioning some parameters such as noise, which fluctuates from a maximum value of 83.2 dB to a minimum of 72.3 dB, showing a downward trend, within environmental quality standards; the behavior of the intensity of the electric field shows a regular behavior, with low values according to environmental quality standards for non-ionizing radiation; The evolution of the carbon monoxide parameter has a very regular and homogeneous upward behavior from a minimum of 149.88 ug/m3 to an increase with a value of 873.3 ug/m3 in the last quarter of 2021, going through a period of constant values of 154. 8 from the year 2019 to 2020; The emission of Particles according to the monitoring has an irregular behavior from an initial value of 11.36 mg/m3N, reaching a minimum of 6.22 mg/m3N, increasing up to a particle concentration of 25.19 mg/m3N, values that are within the normal range of gas emissions from generator sets.